(untitled) (Research, Society and Development, 2021)
This research aims to evaluate the effect of temperature on the degradation of ascorbic acid from osmotically pre-treated passion fruit mesocarp and study its stability during storage. Passion fruit mesocarp slices were dehydrated osmoconvectively (60 °Brix/60 °C) and convectively dried at temperatures of 50, 60 and 70 °C until constant mass. During the drying process, degradation kinetics of the ascorbic acid were carried out and the experimental data was adjusted to match kinetic models of zero and first order. In addition, half-life, activation energy and the reaction coefficient (Q10) were calculated. Slices in natura were osmodehydrated for 90 days of storage and subjected to physical-chemical characterizations. Osmoconvective dehydration promoted a greater incorporation of total soluble solids (19 °Brix) and a lower percentage of water (58.51%) in the passion fruit slices. The drying process reduced the ascorbic acid content, but this compound was better preserved at a temperature of 60 ºC. The first order kinetic model proved to be more suitable to represent the degradation kinetics of ascorbic acid since it presented an activation energy of 83.33 kJ.mol-1. During 90 days of storage, the samples achieved a reduction of 57.43% in ascorbic acid, remaining with a considerable content, 10.77% for the water content and pH below 4.5, making microbial growth impossible, consequently increasing the shelf life.